2009
DOI: 10.1002/lsm.20769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low intensity laser irradiation during healing of skin lesions in the rat

Abstract: This study demonstrates that while clearing wounds of certain bacteria is feasible it does not necessarily translate into a healing advantage. When normal flora are disturbed, environmental organisms more readily colonize the wound surface. It is not clear when using 808 nm light whether the loss of normal flora in the wound alone is responsible for the proliferation of S. aureus or whether the light adds to the effect by stimulating S. aureus growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
(34 reference statements)
1
27
1
Order By: Relevance
“…Dependent on radiant exposure, growth may be increased or decreased; clearing wounds of bacteria is possible using some combinations of wavelength and radiant exposure. In our laboratory, wounds in the rat were cleared of bacteria using red light at radiant exposure of 20 J/cm 2 ; importantly, these sterile wounds healed more slowly than control wounds [22]. We found that 635-nm light at radiant exposure of 1 J/cm 2 produced the most beneficial effects on wound healing, interestingly, without disturbing the normal wound bioburden [22].…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…Dependent on radiant exposure, growth may be increased or decreased; clearing wounds of bacteria is possible using some combinations of wavelength and radiant exposure. In our laboratory, wounds in the rat were cleared of bacteria using red light at radiant exposure of 20 J/cm 2 ; importantly, these sterile wounds healed more slowly than control wounds [22]. We found that 635-nm light at radiant exposure of 1 J/cm 2 produced the most beneficial effects on wound healing, interestingly, without disturbing the normal wound bioburden [22].…”
Section: Introductionmentioning
confidence: 81%
“…Day 8 was selected because the early inflammatory processes should have resolved by this time. Day 19 was selected in order to conclude the study at a standardized time for all animals and when above 70% wound closure could be expected; this was based on pilot work and a previous study [22].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations